Performance and feasibility of self-microsampling of capillary blood and saliva for serological testing of SARS-CoV-2 - Ivonne Morales; Josh Bueggeln; Anna Denzler; Vera Sonntag-Buck; Kathleen Börner; Petr Chlanda; Lisa Koeppel; Andreas Deckert; Till Bärnighausen; Michael Knop; Claudia M. Denkinger (PLoS ONE, 2025)
Background Serology is a valuable tool to estimate infections, case-fatality rates, and immunity. However, venipuncture and clinical infrastructure hinder scalability. This study evaluated the performance, feasibility and user experience of using a microsampling device for self-collected capillary blood and saliva to determine total SARS-CoV-2 S RBD antibodies. Methods It included 149 participants with (n = 48) or without (n = 101) a known history of SARS-CoV-2 infection and confirmed antibodies. Venous and capillary blood were self- or professionally collected from all, and saliva was self-collected by 46/48 participants with antibodies. The detection of SARS-CoV-2 S RBD antibodies in all sample types was tested using a high-throughput platform and agreement was calculated. Intra- and inter-rater agreement between serum and capillary blood in participants with an unknown antibody status was also assessed. Participants evaluated the device’s user-friendliness through questionnaires. Results Among the 48 participants with known past infection and antibodies, agreement was 100% (95% CI: 92.6–100) between serum and capillary blood (self-collected or professionally collected). Self-collected saliva had slightly lower agreement with paired serum samples (95.7%, CI: 85.2–99.5). For the 101 participants without prior evidence of antibodies or infection, serum and self-collected capillary blood had good intra-rater agreement and serum and professionally collected capillary blood had almost perfect intra-rater agreement. Inter-rater agreement was also almost perfect. While 81.8% found the self-finger prick easy, 53.4% found using the microsampler easy. Among those who collected saliva, 84.8% found capillary blood easier to collect compared to saliva (52.2%). Conclusions Our results show that detecting SARS-CoV-2 antibodies from capillary blood and saliva collected with the VAMS microsampling device is feasible and yields valid results. To ensure accuracy and reliability, additional training in self-sampling techniques may be essential. The positive user experience further underscores the microsampling device’s potential for scalable serosurveillance and strengthening pandemic preparedness efforts.